1989
DOI: 10.1172/jci114276
|View full text |Cite
|
Sign up to set email alerts
|

Rat renal epinephrine synthesis.

Abstract: Rats that underwent adrenal demedullation had a 93% decrease in plasma epinephrine (E) levels, but did not decrease their renal E. Even further treatment with 6-hydroxydopamine and reserpine failed to lower renal E levels. Similarly, urine E levels failed to decrease after adrenal demedullation and renal denervation. There is a renal E-synthesizing enzyme that differs from adrenal phenylethanolamine-N-methyltransferase (PNMT) in that it is only weakly inhibited by SKF 29661 and can synthesize epinine from dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…This synthesis was abolished when the kidney was denervated, suggesting that the renal nerves were the main sites of the (urinary) norepinephrine synthesis" 148 • "Several recent studies have demonstrated that dopamine can be generated from L-dopa in the isolated perfused rat kidney, and those findings led to the conclusion that most of the urinary dopamine could be derived from circulating L-dopa (in the kidneys)" 148 • "Recent studies from our laboratory have suggested that urinary NE (norepinephrine) may be derived, in part, from intrarenal sources in man" 149 • "We have previously reported that in standing humans a significant portion of urinary norepinephrine is derived from processes other than glomerular filtration" 149 • "Net production was observed for NE (norepinephrine), DA (dopamine), and NM (normetanephrine) in the renal metabolic compartment, suggesting that a portion of these compounds excreted in the urine may result from intrarenal synthesis or metabolism of these materials" 149 • "… urinary epinephrine may not simply be filtered from the bloodstream" and "urinary epinephrine was derived from the kidney" 150 • "We conclude that appreciable portions of renal and urinary epinephrine are synthesized in the kidney by an enzyme distinct from PNMT". 151 In reviewing the validity of the "spot baseline urinary neurotransmitter testing marketing model" it is important to determine what is being assayed and where it came from. The first assertion of the model claims that it is urinary neurotransmitters that are being assayed.…”
Section: Source Of Urinary Monoaminesmentioning
confidence: 99%
“…This synthesis was abolished when the kidney was denervated, suggesting that the renal nerves were the main sites of the (urinary) norepinephrine synthesis" 148 • "Several recent studies have demonstrated that dopamine can be generated from L-dopa in the isolated perfused rat kidney, and those findings led to the conclusion that most of the urinary dopamine could be derived from circulating L-dopa (in the kidneys)" 148 • "Recent studies from our laboratory have suggested that urinary NE (norepinephrine) may be derived, in part, from intrarenal sources in man" 149 • "We have previously reported that in standing humans a significant portion of urinary norepinephrine is derived from processes other than glomerular filtration" 149 • "Net production was observed for NE (norepinephrine), DA (dopamine), and NM (normetanephrine) in the renal metabolic compartment, suggesting that a portion of these compounds excreted in the urine may result from intrarenal synthesis or metabolism of these materials" 149 • "… urinary epinephrine may not simply be filtered from the bloodstream" and "urinary epinephrine was derived from the kidney" 150 • "We conclude that appreciable portions of renal and urinary epinephrine are synthesized in the kidney by an enzyme distinct from PNMT". 151 In reviewing the validity of the "spot baseline urinary neurotransmitter testing marketing model" it is important to determine what is being assayed and where it came from. The first assertion of the model claims that it is urinary neurotransmitters that are being assayed.…”
Section: Source Of Urinary Monoaminesmentioning
confidence: 99%
“…Most evidence suggests that plasma NE is a more reliable index. More than half of urine NE is apparently derived from the sympathetic nerves that innervate the kidney, 86,87 whereas plasma NE generally has a smaller contribution from local nerves. In addition, urine NE levels are influenced by more metabolic processes than are plasma NE levels, as is illustrated by the fact that only about 10% of plasma NE is excreted unchanged into urine in humans.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…Rat kidney synthesizes E in vivo (10) and lung, heart, and several other peripheral tissues can synthesize E from norepinephrine in vitro (11)(12)(13). Recent studies in adrenalectomized rats demonstrate that extraadrenal E synthesis can play an important regulatory role in animal models of hypertension, diabetes, and glucocorticoid toxicity (14,15).…”
Section: Introductionmentioning
confidence: 99%